Water‐filtered infrared A radiation hyperthermia combined with immunotherapy for advanced gastrointestinal tumours - Pengyuan Liu; Jing Wu; Liting Chen; Zhenhai Wu; Yufei Wu; Ganlu Zhang; Bingqi Yu; Beibei Zhang; Nan Wei; Jinan Shi; Chuanfeng Zhang; Lan Lei; et al. (Cancer Medicine, 2024)
Abstract Introduction This study aimed to validate the effectiveness, safety and feasibility of water‐filtered infrared A radiation (WIRA) whole‐body hyperthermia combined with immune checkpoint inhibitor (ICI) therapy (HIT) and evaluate the real‐world clinical application prospects. Methods This open‐label single‐arm phase 2 clinical trial (NCT06022692) aimed to enrol advanced gastrointestinal tumour (GIT) patients with the MSS/pMMR phenotype. The patients were treated with whole‐body hyperthermia on Days 1 and 8 of each HIT cycle along with administration of tislelizumab on Day 2. Results Between 1 June 2020 and 31 May 2022, 18 patients were enrolled in the study, including those with gastric cancer (n = 6), colon cancer (n = 7), rectal cancer (n = 3) and appendiceal cancer (n = 2). As of 19 May 2023, 17 of the 18 patients had died, including 14 deaths caused by tumour progression and three deaths caused by diseases other than cancer, while one patient was still undergoing follow‐up. In terms of efficacy, the median DCR was 55.6%, while the median PFS and OS were 53.5 days and 134 days, respectively. Four patients (22.2%) experienced immune‐related adverse events, and none of the patients reported grade 3 or higher irAEs. Hyperthermia was followed by an increase in the number of tumour immune‐activated cells. Conclusions HIT can provide survival benefits in patients with GITs by activating antitumour immune function and shows good safety and feasibility.